ANALISA PENGARUH DATA RATE PADA MANET DENGAN MENGGUNAKAN ROUTING PROTOCOL AODV (REAKTIF) - Anisa Widayanti; I Gusti Agung Komang Diafari Djuni; N.M.A.E Dewi Wirastuti (Jurnal SPEKTRUM, 2019)
Mobile Ad hoc Network (MANET) is a dynamic wireless mobile node network, without using network infrastructure such as limited power (because it uses batteries). Mobility of each node that is able to move in all directions, and autonomy of each node in determining its own route to forward the data plan. Therefore, in this study we will see the performance of MANET on IEEE 802.11 g WLAN with a data rate that is different from an AODV routing protocol. This simulation observes changes in data rates ranging from 1, 2.5 Mbps, using WLAN 802.11 g. For parameters used in the data rate starting from 1, 2, 5, Mbps using WLAN 802.11 g obtained the Package Loss value at a data rate of 5 Mbps by 0.98%, the highest value of the highest throughput was generated at a data rate of 1 Mbps of 313,715 bps, and the delay for the data rate of 5 Mbps was 0.0008 second.